Experimental study on seismic behaviors of the welded L-shaped double steel plate-concrete composite shear wall. (December 2021) - He, Wenhui; Wan, Yikun; Li, Yuyu; Bu, JinBin; Deng, Jianliang; Chen, Lin; Zhang, Wenxiao; Wen, Ling
Abstract: A novel type of composite shear wall, composed of L-shaped double steel plates and infilled concrete (LDSCW), was proposed in this paper. In order to study the seismic performance of the LDSCW, the axial ratio and shear span ratio were taken as test parameters and six specimens were designed and tested by the quasi-static loading test. Seismic performances including typical failure characteristics, hysteresis curves, skeleton curves, loading capacity degradation and stiffness degradation, energy dissipation, were analyzed. The LDSCW showed a satisfactory seismic performance during the experiment. The flexural capacity formula of the normal section was also derived and validated by the comparison between the test results and calculated data with errors of within 10%. The study showed when the axial pressure ratio and shear span ratio should be match, which could make more full use of the material property. Graphical abstract: Unlabelled Image Highlights: A new type of shear wall, the welded L-shaped double steel plate-concrete composite shear wall was proposed. The seismic performance of the shear wall structure is studied by means of experimental analysis. The influence of axial compression ratio and shear span ratio on the seismic performance are compared. The calculation formula of bending capacity of the shear wall structure was derived.